Emergence of human-porcine reassortment G9P[19] porcine rotavirus A strain in Guangdong Province, China - Luo, Shicheng; Chen, Xiuqiao; Yan, Guangzhi; Chen, Shengnan; Pan, Jinghua; Zeng, Mengyi; Han, Hui; Guo, Yajing; Zhang, Haoquan; Li, Jiaming; Mo, Meilian; Liu, Mingjie; et al. (Frontiers in Veterinary Science, 2023)
Group A rotaviruses of the family Reoviridae is one of the important intestinal pathogens causing diarrhea in piglets and humans. A human-porcine reassortment rotavirus, GDJM1, was identified from outbreak of diarrhoea in suckling piglets and its associated 60.00% (324/540) morbidity and 20.99% (68/324) mortality in Guangdong Province of China in 2022. Thus, to further characterize the evolutionary diversity of GDJM1, all gene segments were analyzed. The genome constellation was G9-P[19]-I5-R1-C1-M1-A8-N1-T1-E1-H1. Sequence identity and phylogenetic analyses showed that the VP6, VP7, NSP4 and NSP5 genes of GDJM1 were the most closely related to the respective genes of porcine strains, with the highest homology ranging from 95.6598.55% similarity. The remaining seven genes (VP1-VP4, NSP1-NSP3) were the most closely related to human strains, with the highest homology ranging from 91.8396.69% similarity. Therefore, it is likely that GDJM1 emerged as the result of genetic reassortment between porcine and human rotaviruses. To our knowledge, this is the first report that a human-porcine reassortment G9P[19] RVA strain has been identified in mainland China, which providing important insights into evolutionary characterization of G9P[19] RVA strain, and reveals that the strain has a potential risk of cross-species transmission.